Fertility desires, family planning use and pregnancy experience: longitudinal examination of urban areas in three African countries. Issue 1 (December 2015) - Speizer, Ilene; Lance, Peter
Abstract Background Many women have inconsistent fertility desires and contraceptive use behaviors. This increases their risk of unintended pregnancies. Inconsistencies may reflect barriers to family planning (FP) use but may also reflect ambivalence toward future childbearing. Using urban data from Kenya, Nigeria, and Senegal, this study examines the role of fertility desires and FP use behaviors on pregnancy experience over a 2-year follow-up period. Methods Data come from baseline and 2-year follow-up among urban women interviewed in Kenya, Nigeria, and Senegal. At baseline (2010/2011), women were asked about their future fertility desires (want child soon, want to delay >2 years, does not want) and current FP use. At midterm (2012/2013), women were asked if they were currently pregnant or had a birth in the 2-year period. We examine the association between baseline fertility desires and FP use with pregnancy experience and desirability of an experienced pregnancy. Results In the 2-year follow-up period, 27–39 % of women in union experienced a pregnancy or birth. In Kenya and Nigeria, 30–35 % of women using a modern FP method experienced a pregnancy/birth; the percentage with a pregnancy/birth was slightly higher among women not using at baseline (41 % in both countries). In Senegal, the distinction between pregnancy experience between users and non-users was greater (16 % vs. 31 %, respectively). In all countries, pregnancy was less common among users of long-acting and permanent methods; only a small percentage of women use these methods. Women not wanting any(more) children were the least likely to experience a pregnancy in the 2-year follow-up period. No differences were observed between those who wanted to delay and those who wanted soon. Multivariate findings demonstrate distinctions in pregnancy experience by fertility desires among modern FP users. Non-users have similar pregnancy experience by fertility desires. Conclusions Fertility desires are not stable; providers need to consider the fluidity of fertility desires in counseling clients. Programs focusing on new FP users may miss women who are the most motivated to avoid a pregnancy and need to switch to a more effective method; this will result in less unintended pregnancies overall.